A Rational Balance Design of Hybrid Electrolyte Based on Ionic Liquid and Fluorinated Ether in Lithium Sulfur Batteries. Issue 12 (9th July 2019) - Lu, Hai; Chen, Zhen; Yuan, Yan; Du, Huiling; Wang, Jinlei; Liu, Xiao; Hou, Zhenzhong; Zhang, Kai; Fang, Jing; Qu, Yaohui
Abstract : A series of electrolytes based on ionic liquid (IL) N, N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethylsulfonyl) amide (DEMETFSI) and individual or binary co-solvent(s) consisting of 1, 1, 2, 2-tetrafluoroethyl-2, 2, 3, 3-tetrafluoropropyl ether (TTE) and/or 1, 3-dioxolane (DOL) were investigated. The alterative solvent composition results in very different electrolyte properties (conductivity/viscosity, polysulfide solubility and film formation ability) and Li-S cell performances (specific capacity, cycle stability and rate capability). The hybrid system of DEMETFSI/TTE/DOL provides better overall performances compared to the IL with non- or single co-solvent, which is mainly profited from the synergistic function of TTE and DOL, together favorable for the improvement of ionic conduction of the electrolyte and Li surface chemistry. It is further emphasized that the construction of a rational counterbalance between polysulfide dissolution and shuttle suppression is more significant for the advanced Li-S batteries.